2018
DOI: 10.3390/w10050579
|View full text |Cite
|
Sign up to set email alerts
|

Towards Development of an Optimization Model to Identify Contamination Source in a Water Distribution Network

Abstract: Protection of the water system is paramount due to the negative consequences of contaminated water on the public health. Water resources are one of the critical infrastructures that must be preserved from deliberate and accidental attacks. Water qualities are examined at the treatment plant. However, its quality can substantially be contaminated during transportation from the plant to the consumers' taps. Contamination in water distribution networks (WDNs) is a danger that can have severe consequences on publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 160 publications
0
31
0
1
Order By: Relevance
“…An open source water distribution network software, EPANET (version 2.0), developed by the United States Environmental Protection Agency was used in this study (Westlake, OH, USA). EPANET has been widely used in previous studies to model the hydraulic characteristics of a water distribution system, including demand-pressure [29], water age [30,31], water quality, such as chlorine content [18,32] and contaminants [33]. EPANET is also helpful in a new water network design in obtaining the preliminary analysis and information about the hydraulics operation of the proposed area, e.g., the cost-effectiveness analysis of the background leakage control strategy [34].…”
Section: Methodsmentioning
confidence: 99%
“…An open source water distribution network software, EPANET (version 2.0), developed by the United States Environmental Protection Agency was used in this study (Westlake, OH, USA). EPANET has been widely used in previous studies to model the hydraulic characteristics of a water distribution system, including demand-pressure [29], water age [30,31], water quality, such as chlorine content [18,32] and contaminants [33]. EPANET is also helpful in a new water network design in obtaining the preliminary analysis and information about the hydraulics operation of the proposed area, e.g., the cost-effectiveness analysis of the background leakage control strategy [34].…”
Section: Methodsmentioning
confidence: 99%
“…Contamination source identification (CSI) was examined by Adedoja et al [4]. It is a difficult task to derive the source of the contamination from the collected information, and therefore it must be tackled in order to evaluate the spread of the contamination and for immediate remedial strategies.…”
Section: Drinking Water Supply Systemsmentioning
confidence: 99%
“…Nevertheless, its quality may considerably be contaminated during transportation from the treatment plant to the consumers' taps through cross-connections and pipe leakages. The complex nature of Water Distribution Networks (WDNs) allow human interference and therefore, vulnerable to accidental and intentional attacks [1]. Numerous reports have evidently shown that the socio-economic implications of such attacks can be disastrous [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have evidently shown that the socio-economic implications of such attacks can be disastrous [2]- [4]. In recent times, contamination incident in WDNs has been debated as one of the most unhealthy menace to the society that must be addressed [1]- [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation